Relación entre la inversión privada y el crecimiento del sector comercio en la región Loreto durante el periodo 2015–2024 - Rioja Lopez, Alfredo Renan (2026)
This study examines the relationship between private investment and the growth of the commerce sector in the Loreto region between 2015 and 2024. Using a quarterly regional dataset, descriptive statistics are presented and associations among key variables are evaluated primarily through Spearman correlation coefficients. Results show a positive and statistically significant relationship between private investment amounts and the gross value added (GVA) of commerce, alongside robust associations linking the number of registered investment projects, foreign direct investment (FDI), and formal employment in the commerce sector. Monetary investment series and FDI exhibit high volatility and heavy tails, whereas GVA and the stock of formal commercial firms display greater temporal stability. The evidence suggests that investment often acts as a short-term trigger for commercial activity but that its capacity to produce sustained growth depends on project composition, local supply-chain linkages, and institutional quality. These regional findings complement national and multicountry studies and support policy orientations that emphasize investment quality, formalization, and governance to transform episodic investment inflows into enduring improvements in commercial value added and local welfare. The paper contributes to regional policy debates by providing actionable evidence for stakeholders seeking to align investment strategies with inclusive commercial development goals and sustainability.